2021
DOI: 10.3389/fnut.2021.647537
|View full text |Cite
|
Sign up to set email alerts
|

Flavor Characteristics of Ganpu Tea Formed During the Sun-Drying Processing and Its Antidepressant-Like Effects

Abstract: Ganpu tea is a novel type of tea beverage with unique and pleasant flavor that encases Pu-erh tea leaves within an intact mandarin peel. However, to date, no holistic and detail studies on its chemical composition and biological activities have been reported yet. In the present study, by applying UPLC-Q-TOF and UPLC-MS technology, we systematically identified and analyzed 104 water-soluble compounds of Ganpu tea and their variation trend during the sun-drying processing. The results showed that the generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
0
10
2
Order By: Relevance
“…In recent years, high-throughput analytical strategies that coupled liquid chromatography combined with mass spectrometry (LC-MS) (6) and proton nuclear magnetic resonance (1H-NMR) (7) with metabolomics and other multivariate statistical methods (8) are intensively applied for the studies concerning the chemical composition of C. reticulata "Chachi" and pu-erh tea. Sui Xiao et al (9) identified and analyzed 104 water-soluble components of Ganpu tea and their variation trend during sun-drying processing based on ultra-high-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF/MS) technology. Q Exactive-Orbitrap-MS/MS (QE Orbitrap-MS/MS) combines high-performance quadrupole precursor selection with high-resolution, accurate mass Orbitrap detection to deliver high performance and tremendous versatility.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, high-throughput analytical strategies that coupled liquid chromatography combined with mass spectrometry (LC-MS) (6) and proton nuclear magnetic resonance (1H-NMR) (7) with metabolomics and other multivariate statistical methods (8) are intensively applied for the studies concerning the chemical composition of C. reticulata "Chachi" and pu-erh tea. Sui Xiao et al (9) identified and analyzed 104 water-soluble components of Ganpu tea and their variation trend during sun-drying processing based on ultra-high-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF/MS) technology. Q Exactive-Orbitrap-MS/MS (QE Orbitrap-MS/MS) combines high-performance quadrupole precursor selection with high-resolution, accurate mass Orbitrap detection to deliver high performance and tremendous versatility.…”
Section: Introductionmentioning
confidence: 99%
“…The flavor of Ganpu tea is mainly dependent on several factors, such as citrus cultivars, Pu-erh tea resources, and processing technologies. Currently, in the tea market, there are different kinds of Ganpu tea which are made by different citrus cultivars with different maturity (mature, near mature and immature) and various kinds of tea materials (dark tea “Tianjian”, Pu-erh raw tea and ripened Pu-erh tea) ( Qi et al, 2020 , Xu et al, 2021 , Xiao et al, 2021 ). In terms of raw materials, Pu-erh tea and Citrus reticulate Chachi pericarp are commonly used to produce Ganpu tea.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, thousands of enterprises have been involved in the production of citrus tea which was tailored to satisfy consumers' avor desires along with the emergence of food-pairing hypothesis (Spence 2020). Specially, the Citrus Pu-erh tea which was made by peel produced between August and September in Xinhui District of Guangdong, China, and the ripened Pu-erh tea produced in Yunnan, China so-called "Xiao Qing Gan" is the most popular, and is familiar with most consumers (Xiao et al 2021;Yu et al 2018). However, few systematic studies have been conducted on its avor.…”
Section: Introductionmentioning
confidence: 99%
“…The mellow taste and hedonistic aroma of Citrus Pu-erh tea were generated during stu ng fermented tea to citrus pericarps and then redrying them together (Xu et al 2021; Wang et al 2021). During the sun-drying and fermentation process, numerous enzymes and compounds were catalyzed to transform in the citrus peels, producing speci c compounds with a fruity aroma (Xiao et al 2021). For example, avonoid glycosides such as hesperidin and phenolic acids were usually considered to be the critical avor contributors (Xu et al 2021; Zheng et al 2022).…”
Section: Introductionmentioning
confidence: 99%